DAMPAK PERNIKAHAN DIBAWAH UMUR TERHADAP KESEJAHTERAAN RUMAH TANGGA (STUDI KASUS KANTOR URUSAN AGAMA KECAMATAN PLERED KABUPATEN CIREBON) - Dimas Triandiki; E. Sugianto; Edy Setyawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Marriage is a sacred bond between a man and a woman as husband and wife aimed at establishing a harmonious (sakinah) family. Achieving this goal requires not only physical and psychological readiness but also social, economic, emotional, and responsible maturity. The limitation of marriage age constitutes an important principle as regulated in Law Number 1 of 1974 concerning Marriage, which emphasizes that prospective husbands and wives must attain sufficient physical and psychological maturity before entering marriage. However, in Kaliwulu Village, Plered District, Cirebon Regency, the phenomenon of underage marriage remains prevalent and affects household welfare. This study aims to analyze the factors causing underage marriage and its impact on household welfare at the Office of Religious Affairs (KUA) of Plered District. This research employed a descriptive qualitative approach, collecting data through interviews, observations, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing, supported by relevant literature review. The findings reveal that the primary factor contributing to underage marriage is personal willingness influenced by premarital relationships, with parental approval granted to avoid social stigma and accompanied by parental supervision. Underage marriage significantly affects household welfare due to the instability of emotional maturity and personal integrity in resolving conflicts, resulting in increased parental burdens and limited independence of the couple.